Visionary Leadership Styles of School Principals in the Era of Independent Learning: Challenges and Implementation Strategies - Habibah, Sitti (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Under the Merdeka Belajar national policy, the high school principal implements a visionary leadership style. To implement Merdeka Belajar, school leaders must drive change, foster an adaptive educational vision, and innovate learning. The main issues are the discrepancy between the expectations of the Merdeka Belajar policy and the school's conventional managerial practices, as well as the challenges of mobilizing High School 3 Gowa's teaching and education staff to support this vision of change. This study aims to (1) describe the principal of the high school visionary leadership model within the Merdeka Belajar framework, (2) identify internal and external challenges to implementing this vision, and (3) formulate specific strategies the principal has used to overcome these challenges and encourage school transformation. This qualitative study adopts a single-case study strategy. In-depth interviews with the principal, vice principal, and teacher representatives; Merdeka Belajar implementation documentation; and direct observation of High School 3 Gowa activities collected data. This study found that the principal at High School 3 Gowa's visionary leadership style was realized through open collaboration, teacher autonomy in curriculum design, and digital technology to accelerate the vision. The key hurdles included senior instructors' initial opposition, insufficient resources for new training, and the need to improve digital literacy. A core change team (Agent of Change) and teacher coaching were the main implementation techniques. This study provides an empirical model and examples of best practices for visionary leadership at a specific educational unit level to help high school principals and Indonesian high school principals succeed with Merdeka Belajar.